EFEKTIVITAS VIDEO PEMBELAJARAN ANIMASI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Mita Mita Aswatun; Haifaturrahmah; Nursina Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Animated educational videos are a potential innovation for improving the quality of learning through the presentation of interesting and interactive material. This study aims to identify, review, and synthesize various empirical findings regarding the effectiveness of using animated educational videos in improving the motivation and learning outcomes of elementary school students. The research method applied is a Systematic Literature Review (SLR) with a qualitative approach, which aims to obtain a comprehensive understanding and systematic synthesis of the available scientific evidence. Literature searches were conducted using the Google Scholar, SINTA, and DOAJ databases with a publication range of 2020–2025. The results of the study indicate that the use of animated videos significantly contributes to increasing student motivation, active engagement, and conceptual understanding through the presentation of interesting and interactive material. The effectiveness of this medium is greatly influenced by the readiness of infrastructure, teacher competence and creativity, and the suitability of media characteristics to student needs.